Analisis Formulasi American Coookies Puree Kulit Pisang Kepok (Musa Paradisiaca Linn) Berdasarkan Daya Terima Konsumen - Zahrakusumah, Alysha Emma; Dahlia, Mutiara; Mahdiyah, Mahdiyah (Sahabat Publikasi, 2024)
Kepok banana peel puree is used in making American cookies as an effort to utilize local food. The research was conducted to analyze the effect of the formulation using kepok banana peel puree in the manufacture of American cookies on consumer acceptance. This research was conducted at the Pastry and Bakery Processing Laboratory, Culinary Education Study Program, Faculty of Engineering, Jakarta State University. The method used in this research is the experimental method. The research sample was American cookies with the use of kepok banana skin puree with a percentage of 10%, 20% and 30%. Then it was tested on 25 slightly trained panelists who assessed aspects of color, aroma, taste, inner texture, outer texture, crumb, and shape. In this research, it is expected to obtain modifications of American cookies with kepok banana peel puree which are preferred and rich in fiber and can optimize the utilization of kepok banana peels as a functional local food. From the results of the Friedman test, the best treatment is the result of the kepok banana peel puree formulation as much as 20%.